Direct and moderating effects of community context on the psychological well-being of African American women - Brown, P. Adama (2000)
The effects of community characteristics on well-being were examined among 709 African American women. Direct and moderating effects of neighborhood characteristics on distress were tested. Aggregate-level ratings of neighborhood cohesion and disorder were significantly related to distress, although the relation between cohesion and distress became nonsignificant when individual risk factors were statistically controlled. Aggregate-level neighborhood variables interacted significantly with individual risk and resource variables in the prediction of distress, consistent with trait-situation interaction theories (D. Magnusson & N. S. Endler, 1977). Community cohesion intensified the benefits of a positive life outlook. Community disorder intensified both the benefits of personal resources and the detrimental effects of personal risk factors. Results showed evidence of resilience among African American women